Professional Quality of Life among Oncology Nurses at Turkish Palestinian Friendship Hospital in Gaza Strip - Tareq Khattab; Yousef Aljeesh (KHD-Production, 2022)
Purpose: Study was conducted to identify the positive and negative aspects of professional quality of life among nurses at the Turkish Palestinian Friendship Hospital in Gaza Strip, as well as to look into the relationship between sociodemographic factors and professional quality of life among nurses at the Turkish Palestinian Friendship Hospital in Gaza Strip. Method: A descriptive cross-sectional design. The Professional Quality of Life Scale (ProQoL), version 5, was used to collect data from 74 nurses who participated in the study, with an 84% response rate. Results: Study participants had high levels of compassion satisfaction (M= 3.9068; SD= 0.86979; WM 78.1%), moderate level of burnout (M= 3.2784; SD= 0.60845; WM 65.5%), and moderate level of secondary traumatic stress (M= 3.0027; SD= 0.77211; WM 60%). There are statistically significant determinants for compassion satisfaction with age group up to 40 years and older (F= 3.406, P= 0.039), participants who received oncology education (T = 2.297, P= 0.025). Also, there is a significant relationship between age group